Corporate leniency with private information: The push of prosecution and the pull of pre-emption - Joseph E. Harrington (The Johns Hopkins University, Department of Economics, 2011)
A corporate leniency program provides relief from government penalties to the first member of a cartel to come forward and cooperate with the authorities. This study explores the incentives to apply for leniency when each cartel member has private information as to the likelihood that the competition authority will be able to convict them without a cooperating firm. A firm may apply for leniency because it fears being convicted or because it fears another firm will apply. Policies by the competition authority to magnify concerns about pre-emption - and thereby induce greater use of the leniency program - are explored.
Keywords: 330